Ensilaje de pasto Estrella Africana (Cynodon nlemfuensis) con la adición de melaza, suero de leche e inóculos microbiales (UNED Research Journal, 2014)
ABSTRACT: African Star grass silage with molasses, whey and microbial additive. Nutritional and fermentation value of African star grass (Cynodon nlemfuensis) silage with application of molasses, mixtures of whey and molasses, and microbial inoculants were determined in the University of Costa Rica campus during 2009. Forage was harvested with 60 days of regrowth to 80cm height and ensiled for 60 days in transparent plastic bags of one kilogram capacity. The treatments consisted in homemade inoculum (1 l/t MF), commercial inoculum (3,76g/t MF) and without application of inoculum, which were included molasses (3% p/p), mixtures of molasses and whey (3% p/p) in three relationships (2:1, 3:1 and 4:1) and a control without application of sources of sugars for a total of fifteen treatments with four replicates per treatment. The homemade inoculum decreased the DM content (26,42±0,70%) and increased CP concentration (11,68±0,20%), ash (12,74±0,14%), NDF (64,88±2,02%), ADF (36,51±1,53%), lignin (4,29±0,39%), pH value (4,56±0.27), buffer capacity (91.20±3.34 mEqNaOH.100g-1DM) and ammonia nitrogen (1.78±0.28%) (N/N total). On the other hand, the commercial inoculant decreased the NDF content (63,00±1,57%) and the lignin content (2,87±0,17%) and buffer capacity (76,87±8,77mEqNaOH/100g DM) of materials. Molasses and mixtures of molasses and whey application, increase DM, NDF, ADF, IVDMD, pH and ammonia nitrogen (N/N total). Homemade microbial inoculant reduced the energy density of the material. The results show that the better fermentative and nutritional value of silage was obtained with the application of mixture molasses and buttermilk in a 4:1 ratio with no inoculum added. KEYWORDS: Crude protein, total digestible nutrients, neutral detergent fiber, carbohydrate source, homemade inoculum